Mechanisms and Parameters of the Binding of Amitozinoberamid to DNA in the Aqueous Solution - Kutovyy, S. Yu.; Savchuk, R. S.; Bashmakova, N. V.; Hovorun, D. M.; Zaika, L. A. (Ukrainian Journal of Physics, 2018)
The interaction between the amitozinoberamid preparation (thiotepa-alkylated berberine) and a DNA macromolecule in the aqueous solution has been studied, by using the optical spectroscopy methods: electron absorption and fluorescence. The dependence of spectral characteristics on the concentration ratio N/c between the DNA base pairs and the ligand molecules is plotted. Using the system of modified Scatchard and McGhee–von Hippel equations, the parameters of the binding of amitozinoberamid to DNA are determined. A comparative analysis of the DNA interaction with amitozinoberamid, on the one hand, and berberine and sanguinarine alkaloids, on the other hand, is carried out. The structure and the spectra of electron absorption of thiotepa, berberine, and amitozinoberamid molecules are calculated in the framework of the density functional theory at the DFT B3LYP/6-31G(d,p) level.